Assessment of simultaneous incorporation of crumb rubber and asphaltite in asphalt binders - Javier Eduardo Mantilla-Forero (Dyna, 2019)
Every day, roads are submitted to greater stresses. Thereby, additives have been incorporated to asphalt mixtures to enhance pavements performance. The purpose of this experimental study is to characterize for the first time, to date, the viscoelastic properties of asphalt samples modified with recycled rubber -from used vehicles tires- and asphaltite in the same mixture, at different temperatures and frequencies. All with the aim of optimizing the material properties and coming up with a proposal to an environmental issue: discarded vehicles tires and their after-service use. The stiffness of briquettes was analyzed by axial compression test. The results were principally represented in Black Space and Cole-Cole plot and indicate a substantial increase in stiffness and elasticity of the modified asphalt throughout the whole temperature range. This shows that the simultaneous addition of these two ingredients to the bitumen is a favorable alternative in road construction using asphalt pavements.